Developing an evaluation tool to provide a 360-degree reflection on work-integrated learning in accounting education. (2nd November 2021) - Lewis, Gemma K.; Williams, Belinda; Allen, Stephen; Goldfarb, Beverly; Lyall, Kevin; Kling, Rose; Statham, Peta
ABSTRACT: In the higher education environment, work-integrated learning (WIL) is widely considered a key component of developing work-ready and professional graduates. Quality evaluation systems are needed to ensure continual improvement and development of WIL programs focusing on all stakeholder perspectives, not just the students or the sponsoring organisations. This paper describes the process a team of business academics and educational developers at an Australian university adopted to design a 360-degree approach to WIL evaluation, using action research methodology. The team developed an evaluation tool, comprising an online survey and associated web-enabled platform. The tool was trialled in a final year accounting unit, which had recently introduced a placement-based WIL project. Peer reflections from WIL educators across our institution in addition to internal testing, complemented our findings regarding what further changes were required to make this innovative tool applicable to different WIL contexts and disciplines.